DoE implementation for Telmisartan and hydrochlorothiazide drug-drug cocrystal synthesis to enhance physicochemical and pharmacokinetic properties - Gunjan Vyas, Jigar Shah, Shery Jacob (Journal of Applied Pharmaceutical Science, 2023)
Telmisartan (TEL) and Hydrochlorothiazide (HCT) fixed-dose drug combination (FDC) is proven to be more effective for the treatment of hypertension, as compared to the administration of TEL or HCT alone. Commercially available FDC of TEL and HCT involves the usage of alkalizers in the tablet formulation, to maintain a microenvironmental pH for solubility enhancement of drugs in physiological conditions. This usage of alkalizer makes them prone to moisture uptake during storage. An attempt has been made to tackle the moisture sensitivity of FDC formulation and to improve solubility and bioavailability using the cocrystallization technique. A drug-drug cocrystal synthesis of TEL and HCT has been performed by implementing the design of experiment (DoE) approach. Molar ratios, different manufacturing techniques, and the usage of different solvents for synthesis were evaluated systematically, by applying the statistical DoE concept. Prepared cocrystals were evaluated for various In-vitro characterization analysis tests such as melting point, Differential scanning calorimeter, X-ray powder diffraction, Dynamic vapour sorption, saturation solubility, assay, dissolution, and In-vivo study. Based on the evaluation, it was established that the new crystal lattice of the TEL: HCT in a 1:1 ratio was successfully synthesized. Additionally, the drug: drug cocrystal was found to be stable at accelerated stability conditions, indicating a stable crystal lattice. This TEL: HCT cocrystal is formulated into tablet dosage form using excipients equivalent to commercially available tablets (except alkalizer). The tablet dosage form incorporated with this novel drug-drug cocrystal demonstrated improved solubility, pharmacokinetic parameters and formulation not susceptible to moisture uptake.
Keywords: Telmisartan (TEL), hydrochlorothiazide (HCT), drug-drug cocrystal, fixed dose combination (FD